False alarm study: False alarm data collection and analysis from fire detection and fire alarm systems in selected European countries. - (:unkn) unknown (E. Schmidt, 2018)
The book deals with carefully examined statistics on fires and, in particular, the number of fire alarms due to fire detection and fire alarm systems and the false alarm rate. The book describes a scientific approach on how to qualify and quantify the problem of false alarms. At the same time, this is being applied on several European countries. The topic is indeed related to a specific issue, but it provides impulses for a very broad spectrum of similar problems (e.g. Fake News).
Keywords: Brandmelder; Brandfall; Ursachenanalyse; Feueralarm; Fehlalarm; Häufigkeit; Internationaler Vergleich